Potential of Hibiscus sabdariffa Linn. polyphenol-rich extract in improving diabetes-induced vascular functional and structural abnormalities in rats - Fatin Farhana Jubaidi,; Satirah Zainalabidin,; Lai, Ying; Nur Liyana Mohammed Yusof,; Siti Balkis Budin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Hibiscus sabdariffa Linn. contains a high concentration of polyphenolic compounds and shows potentials in reducing vascular complications in diabetes mellitus (DM) patients. This study was aimed to determine the ability of H. sabdariffa Linn. polyphenol-rich extract (HPE) in improving vascular endothelial dysfunction and attenuating oxidative stress in type 1 DM. DM was induced in adult male rats and the rats were then divided into three groups; untreated DM (DM); DM with HPE supplementation (DM+HPE); and DM with metformin (DM+MET). Another group of non-diabetic rats served as the normal control group. These rats were left untreated for four weeks before being subjected to the supplementations for another four weeks. The thoracic descending aorta was isolated from the treated and untreated rats to measure the vascular reactivity, oxidative stress, and morphological alterations. The results showed that HPE supplementation significantly reduced the systolic blood pressure (SBP) and mean arterial pressure (MAP) in the DM+HPE group (p<0.05). HPE also showed a tendency to improve endothelium-dependent vasorelaxation compared to the untreated diabetic rats. Rats treated with HPE exhibited a considerable improvement in the activities of antioxidants and significantly attenuated oxidative damage (p<0.05). Histological findings showed that HPE supplementation improved morphological changes in the aorta. In conclusion, HPE supplementation reduces vascular abnormalities in DM condition probably via amelioration of oxidative stress.